Safety and efficacy of a novel algorithm to guide decision-making in high-risk interventional coronary procedures. (15th January 2020) - Al-Rashid, Fadi; Totzeck, Matthias; Mahabadi, Amir A.; Johannsen, Laura; Luedike, Peter; Lind, Alexander; Krueger, Andrea; Kamler, Markus; Kahlert, Philipp; Jánosi, Rolf Alexander; Heusch, Gerd; Rassaf, Tienush
Abstract: Background: Patients with severe coronary artery disease (CAD), comorbidities, or impaired hemodynamics are at risk during percutaneous coronary interventions. The aim of the study was to investigate the safety and efficacy of a novel risk-stratification algorithm for high-risk coronary procedures. Methods and results: We prospectively screened 1189 patients with CAD requiring revascularization (period 07/2017–06/2018). The algorithm was designed to select high-risk procedures. Patients with elevated risk ( n  = 150) were classified into 3 risk groups (high-risk intervention [HRI] I–III) and procedural management was adjusted according to HRI group. Overall, 55 patients were categorized as HRI I, 52 as HRI II, and 43 as HRI III. With increasing HRI-level, SYNTAX score increased (HRI I:15 ± 5% vs. HRI II:24 ± 8% vs. HRI III:34 ± 7%; p  < 0.001), and ejection-fraction decreased (HRI I:48 ± 10% vs. HRI II:49 ± 10% vs. HRI III:40 ± 11%; p  < 0.001). The primary endpoint (hemodynamic compromise requiring mechanical circulatory support [MCS] [HRI I/II], unsuccessful weaning from MCS in the catheterization laboratory[HRI III], or periprocedural death[HRI I–III]) occurred in no case. The secondary endpoint of hemodynamic deterioration occurred in 26% ( n  = 39) but did not result in hemodynamic instability due to the risk-adjusted procedural management. The composite endpoint of in-hospital major adverse cardiac and cerebrovascular events (death, new myocardial infarction, cerebrovascular accident) occurred in 4 patients (3%). Conclusions: The novel algorithm is a safe team-based stratification method for the identification and management of patients undergoing high-risk coronary interventions. Highlights: there is an unmet need for risk stratification and reduction in high-risk PCI novel risk-stratification algorithm that integrates anatomical complexity, comorbidity, and clinical presentation, including hemodynamic status use of this algorithm was associated with no periprocedural hemodynamic instability and a low in-hospital MACCE